TRAIN YOUR BRAIN : The ultimate 21 day mental skills programme for peak performance - Alder, Harry, Dr. author 289476 (London, United Kingdom : Piatkus, 1997)
This is a neurobiological discussion of what it means to operate in a state of "flow", or peak performance, when anything and everything seems possible. Alder explains how to identify and "capture" this heightened state, and provides simple practical exercises and examples of what may be achieved.